Vaginal Endosalpingiosis Case Report: A Rare Entity Presenting as Intermenstrual Bleeding - Sara Câmara; Gustavo Mendinhos; Rosa Madureira; Amália Martins; Carlos Veríssimo (Case Reports in Obstetrics and Gynecology)
Endosalpingiosis is a benign and rare entity whose pathophysiology remains unknown. It has been described in pelvic organs, the abdomen, or axillar lymph nodes. Its underrecognition has occasionally led to its misinterpretation for an adenocarcinoma. This case reports the treatment and follow-up of vaginal endosalpingiosis, presenting as a vaginal polyp in a premenopausal women with intermenstrual bleeding. To our knowledge this is the first reported case of vaginal endosalpingiosis and the second mucosal localization after bladder endosalpingiosis.